2007
DOI: 10.1177/1534735407301632
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Use of Milk Thistle (Silybum marianum)

Abstract: Milk thistle (Silybum marianum) is an herbal supplement used to treat liver and biliary disorders. Silymarin, a mixture of flavanoid complexes, is the active component that protects liver and kidney cells from toxic effects of drugs, including chemotherapy. Although milk thistle has not significantly altered the course of chronic liver disease, it has reduced liver enzyme levels and demonstrated anti-inflammatory and T cell-modulating effects. There is strong preclinical evidence for silymarin's hepatoprotecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(108 citation statements)
references
References 48 publications
0
98
0
10
Order By: Relevance
“…Among the studies reviewed here, there are few which have indicated antitumor activity in vivo such as topotecan (Yakushiji et al, 1997), mixture of flavonoids complexes in milk thistle (Post-White et al, 2007) and ellagic acid (Misikangas et al, 2007;Seeram et al, 2007). Raddeanin A, a triterpenoid saponin from Anemone raddeana has also demonstrated good antitumor activity.…”
Section: Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the studies reviewed here, there are few which have indicated antitumor activity in vivo such as topotecan (Yakushiji et al, 1997), mixture of flavonoids complexes in milk thistle (Post-White et al, 2007) and ellagic acid (Misikangas et al, 2007;Seeram et al, 2007). Raddeanin A, a triterpenoid saponin from Anemone raddeana has also demonstrated good antitumor activity.…”
Section: Mechanismsmentioning
confidence: 99%
“…It is the active component of milk thistle (Silybum marianum), consisting of a mixture of flavanoid complexes and have been found to exert anticarcinogenic effects in preclinical trials. It was reported that the anticancer property was indicated by its ability to inhibit the growth of cancer cells including cervical cancer cells (Post-White et al, 2007).…”
Section: Flavonoidsmentioning
confidence: 99%
“…It has been shown that silibinin inhibits overproduction of O 2 À. by stimulated neutrophils, xanthine oxidase activity, and prevents hem-mediated oxidative modification of low density lipoproteins. 39,42 Methods…”
mentioning
confidence: 99%
“…Sample 5 was prepared by defatting 5 g of the powdered seeds with 250 mL of petroleum ether (boiling point 40-60 °C) by cold maceration while in the case of sample 6, the seeds were defatted with 250 mL of petroleum ether (40-60 °C) using a Soxhlet apparatus. The defatted powders were treated similarly as samples (1)(2)(3)(4). Triplicate 20-µL injections were made for each sample; they were chromatographed under the specified conditions described previously, and the peak areas were measured (Figs 3 and 4).…”
Section: Chromatographymentioning
confidence: 99%
“…1), is the active component isolated from the seeds and fruits of the plant. Silymarin proved to protect liver and kidney cells from toxic effects of drugs including chemotherapy [3]. In vitro experiments with kidney cells damaged by paracetamol, cisplatin, and vincristin demonstrated that administration of silymarin can obstruct the nephrotoxic effects [4].…”
Section: Introductionmentioning
confidence: 99%